Six-feature star-pattern identification algorithm - Scholl, M S (Applied optics (2004), 1994)
A six-feature all-sky star-field identification algorithm is developed. The minimum identifiable starpattern element consists of an oriented star triplet defined by three stars, their celestial coordinates, and their visual magnitudes. The performance of the star-pattern identification algorithm is verified through the use of software simulation.